Circulating chemokines and leukocytes and their impact on breast cancer prognosis - Rogério Agenor de Araújo; Felipe Andrés Cordero da Luz; Eduarda da Costa Marinho; Camila Piqui Nascimento; Ana Cristina Araújo Lemos da Silva; Maria Luíza Gonçalves dos Reis Monteiro; Marcelo José Barbosa Silva (Discover Oncology)
Abstract Introduction Tumor staging (TNM) and immunohistochemistry (IHC) are established predictors of breast cancer (BC) prognosis, but there are modulations by the tumor microenvironment and serum factors. This study aims to evaluate circulating chemokines, cytokines and leukocytes in the blood of patients with BC. Methods A prospective study involving 200 women with infiltrative breast carcinoma was conducted. Patients were stratified by TNM stage and IHC subtype for survival analysis and correlations with the Neutrophil-to-Lymphocyte Ratio (NLR) and the expression of 13 chemokines and 3 cytokines. Results Survival was significantly higher in women with early-stage tumors (I/II) and in Luminal A and HER2 + subtypes. No significant differences in NLR were observed across TNM stages or IH subtypes. Among the 172 non-metastatic patients, those with NLR > 2 had shorter disease-free survival (DFS) (multivariate analysis). In the Luminal B subgroup, patients with NLR > 2 exhibited worse progression-free survival (PFS) (multivariate analysis), while in the triple-negative (TN) subgroup NLR > 3 was associated with poorer overall survival (OS) (univariate analysis). NLR was prognostic during follow-up, with lower OS observed in patients with NLR > 3 at 12 months post-diagnosis. Significant correlations were identified among 8 CC/CXC chemokines. Furthermore, leukocyte count was significantly correlated with IL-6, RANTES/CCL5, and GRO-Alpha/CXCL1; lymphocytes with MCP1/CCL2; and monocytes with IP10/CXCL10. NLR was significantly correlated with RANTES/CCL5. Conclusion Risk stratification in BC patients is grounded in tumor staging and immunohistochemistry. However, systemic inflammatory responses, including cytokine- and chemokine-mediated signaling of neutrophils and lymphocytes, play a critical role in modulating prognosis.